Funções trigonométricas no contexto dos registros de representação semiótica: uma análise em livros didáticos - COSTA, Renata Gaspar da (2022)
This research seeks to answer the following question: does the approach to the trigonometric cycle content, specifically the sine and cosine functions, in the textbook include aspects of the theory of semiotic representation registers according to Raymond Duval? The general objective is to analyze how the approach to the content of trigonometric functions sine and cosine in high school textbooks, approved by the Plano Nacional do Livro Didático - PNLD 2021, contemplates the fundamental hypothesis of the theory of semiotic representation registers by Raymond Duval. The research involved the analysis of two Mathematics textbooks that were approved in the PNLD-2021, aimed at High School, and the data collection and analysis procedures were subsidized by Laurence Bardin's Content Analysis. In both analyzed books, it was observed that the authors mobilize several records of mathematical representation, however, this mobilization alone does not characterize the use of Duval's theory. It is not enough just to collect records, it would be necessary to articulate the significant units of each record with each other so that the reader has a global view of the mathematical object. It was also noted that both books try to articulate the records of algebraic representation and graphic representation, however, the association between the significant units of these records did not occur completely.